Trends in Marketing Communication: Strategic Influencer Marketing for Sustainable Presence - Irene Silviani; Eko Pamuji; Meithiana Indrasari (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2026)
This article investigates contemporary trends in marketing communication by focusing on strategic influencer marketing as a communicative practice for sustaining brand presence in digital environments. Drawing on a communication studies perspective, the study analyzes how meanings, relationships, and credibility are co-constructed among brands, intermediaries, and audiences witplatformizeder ecosystems. The research employs a qualitative design using semi-structured interviews with three KOL specialists, one marketing agency officer, two café owners, and five micro and nano influencers, capturing the interaction between institutional actors and everyday content creators. The findings indicate that sustainable presence in influencer-based communication is shaped by three interrelated dynamics: discursive alignment between brand and influencer values, ongoing dialogic engagement with audiences, and flexible collaboration formats responsive to platform-specific cultures. Micro and nano influencers emerge as particularly salient in cultivating intimate, niche communities and reinforcing trust-based, peer-like communication with followers. The study argues that influencer marketing should be understood not merely as a promotional technique but as a relational communication strategy that integrates branding, mediated interpersonal interaction, and community building. These insights extend debates on digital marketing communication and offer implications for practitioners and scholars concerned with strategic, sustainable communication in platformized media environments